A Comparative Analysis between Online and Offline English Learning in Covid-19 Pandemic Era: Students’ View - Agus Rahmat (UIR Press, 2022)
The objectives of this research were to find out which is the more effective learning between online and offline English learning, and the strengths and weaknesses of online learning and offline English learning. A descriptive qualitative research design was used in this research. The results of the research showed that all of the participants perceived that offline learning is more effective than online learning for many kinds of reasons such as offline learning can know and feel the situation directly in the learning process, teamwork is better in offline learning, students focus more to the teachers’ explanation delivered in the classroom. Then, the strengths of online learning are the time, place and condition are flexible and it is able to maintain the teaching and learning process during the Covid-19 pandemic. The weaknesses of online learning are limited interactions among the students, network constraints, and students’ out of control issues. Besides, the strength of offline learning is the ability to interact and share directly in the classroom as well as easy to comprehend the material while the weaknesses of offline learning are the time and place are not flexible and the risk of contagion.